Developing type 1 diabetes resources: a qualitative study to identify resources needed to upskill and support community sport coaches - Lim, Rachel J.; Roberts, Alison G.; O’Dea, Joanne M.; Shetty, Vinutha B.; Roby, Heather C.; Davis, Elizabeth A.; Teo, Shaun Y. M. (Frontiers in Clinical Diabetes and Healthcare, 2023)
Introduction: Community sport coaches in Western Australia lack an understanding, the confidence, and knowledge in supporting young people with Type 1 diabetes (T1D). This study aims to identify what T1D educational resources are required to upskill coaches in Western Australia.Methods: Semi-structured online interviews were conducted with i) young people living with T1D, ii) parents of young people living with T1D and iii) community sport coaches. The questions explored i) past experiences of T1D management in community sport ii) the T1D information coaches should be expected to know about and iii) the format of resources to be developed. Thematic analysis of interview transcripts was performed, and the themes identified were used to guide resource development.Results: Thirty-two participants (16 young people living with T1D, 8 parents, 8 coaches) were interviewed. From the interviews, young people wanted coaches to have a better understanding of what T1D is and the effect it has on their sporting performance, parents wanted a resource that explains T1D to coaches, and sports coaches wanted to know the actions to best support a player living with T1D. All groups identified that signs and symptoms of hypoglycaemia and hyperglycaemia needed to be a key component of the resource. Sports coaches wanted a resource that is simple, quick to read and available in a variety of different formats.2The interviews resulted in valuable information gained from all groups and have reinforced the need for the development of specific resources to increase community knowledge and provide support for players with T1D, parents and sport coaches.